2022
DOI: 10.1002/cbdv.202100900
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Evaluation, and Molecular Modeling Studies of New Thiosemicarbazide‐Triazole Hybrid Derivatives of (S)‐Naproxen

Abstract: The discovery of new antimicrobial molecules is crucial for combating drug‐resistant bacterial and fungal infections that pose a dangerous threat to human health. In the current research, we applied a molecular hybridization approach to synthesize original thiosemicarbazide‐triazole derivatives starting from (S)‐naproxen (7a–7k). After structural characterization using FT‐IR, 1H‐NMR, 13C‐NMR, and HR‐MS, the obtained compounds were screened for their antimicrobial activities against Staphylococcus aureus ATCC 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The tests showed a moderate potential of the tested compounds against S. aureus ATCC 29213 and MRSA. The demonstrated MIC value against two strains of S. aureus was similar to that demonstrated by our compounds and was in the range of 64–256 μg/mL [ 19 ]. D. Bhakiaraj et al, in a study from 2021 also showed the potential of compounds from the group of thiosemicarbazides with tetrazole ring against strains belonging to S. aureus [ 17 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The tests showed a moderate potential of the tested compounds against S. aureus ATCC 29213 and MRSA. The demonstrated MIC value against two strains of S. aureus was similar to that demonstrated by our compounds and was in the range of 64–256 μg/mL [ 19 ]. D. Bhakiaraj et al, in a study from 2021 also showed the potential of compounds from the group of thiosemicarbazides with tetrazole ring against strains belonging to S. aureus [ 17 ].…”
Section: Resultssupporting
confidence: 75%
“…In recent years, scientists have been interested in the use of small organic molecules, including heterocyclic compounds, as promising therapeutic substances [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Literature data from our review indicate that 1,3,4-thiadiazole derivatives and intermediates in their synthesis, 1,4-disubstituted thiosemicarbazides, are commonly reported as promising antimicrobial agents [ 1 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Compounds containing these structures often show higher activity than standard antibacterial drugs, such as penicillin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One group of substances among which it is justified to search for new compounds with possible uses in the treatment of infectious diseases is thiosemicarbazide derivatives. There are many research studies showing their anti-tuberculosis [ 6 ], antiviral [ 7 ], and antibacterial properties [ 8 , 9 , 10 , 11 , 12 , 13 ]. Compounds from the group of thiosemicarbazide derivatives are synthesized not only as potential bioactive molecules but also as precursors for the synthesis of heterocyclic compounds, such as thiadiazoles, oxadiazoles, and triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazine-1-carbothioamide (3-thiosemicarbazide) derivatives received considerable attention owing to their diverse chemotherapeutic activities [ 1 ]. Several mono- and di-substituted- N -hydrazine-1-carbothioamides were reported to possess marked anticancer [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], antifungal [ 10 , 11 , 12 ], antituberculous [ 13 , 14 , 15 ], antiviral [ 16 , 17 ], antibacterial [ 18 , 19 , 20 , 21 , 22 ], and antiprotozoan activities [ 23 , 24 , 25 , 26 ]. In addition, several hydrazine-1-carbothioamide derivatives were recognized as potent urease inhibitors [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%